Etika Penggunaan Teknologi AI Menurut Paul Ricoeur Sebagai Realisasi Hidup Baik - FRANSESCO AGNES RANUBAYA; SIRILUS ANANTHA DEVA HEXANNO; REGINALD; FX. EKO ARMADA RIYANTO (Universitas Insan Budi Utomo, 2024)
This research focuses on analyzing the ethical use of artificial intelligence (AI) technology with reference to the views of philosopher Paul Ricoeur. The background involves the rapid growth of AI technology and the need to understand its impact on society as well as individuals, with an emphasis on ethical and moral aspects. The aim of this research is to identify ethical principles that can serve as guidelines in the development and application of AI technology, as well as to apply Ricoeur's views on the realization of the good life in the context of technology. The research methodology includes a philosophical analysis of Ricoeur's work, a literature review on the ethics of AI technology, and a case study of the implementation of ethics in a particular AI project. The results show that the application of Ricoeur's ethical principles can guide the development of more humane and responsible AI technologies. The research conclusions emphasize the need for human involvement in AI decision-making, transparency, and moral considerations in the implementation of such technologies. The contribution of this research to science involves an in-depth investigation of Ricoeur's views in the context of AI technology as well as providing a conceptual foundation for the development of AI ethics oriented towards the realization of the good life and social welfare